Root Cause Analysis of the Decline in Surplus Earnings at Koperasi Bina Warga in 2024 - Puji Nadiya Nurdini; Andri Indrawan; Evi Martaseli (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the factors and root causes contributing to the decline in Surplus Earnings at Koperasi Bina Warga in the 2024 period. A descriptive qualitative method with a case study approach was employed to identify and analyze these contributing factors. Data were collected through in-depth interviews with the cooperative’s chairperson, secretary, and treasurer, and were further supported by documentation and direct observation. The results indicate that the decline in SHU was caused by a decrease in member loan activity, low member participation, a high rate of non-performing loans, restrictions on savings, and a reduction in the number of cooperative members. Through the application of Root Cause Analysis using the 5 Why Analysis and Fishbone Diagram approaches, the decline in loan activity was identified as the primary root cause. Data validity was ensured through the use of methodological triangulation, source triangulation, and time triangulation. The study recommends optimizing loan services, enhancing member participation, controlling non-performing loans, and developing digital services to strengthen cooperative performance and increase future surplus earnings.